Pengaruh Modal Sendiri, Perputaran Kas, Perputaran Piutang Dan Marjin Laba Terhadap Rentabilitas Ekonomi Pada Koperasi Di Bandar Lampung - Nur Faizah; Hardini Ariningrum; Kusnadi Kusnadi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2015)
Abstract, This study aimed to determine the effect of their own capital, cash turnover, receivables turnoverand profit margin of profitability of economic cooperation in Bandar Lampung. The object of the study was 5Cooperative in Bandar Lampung. The analysis tool diguanakn is Normality Test, Test Classical Assumption,Regression Testing, Test-T, and Test-F where processing the data using SPSS version 17. The results showedthat the partial capital itself does not affect the economic profitability. Meanwhile, cash turnover, receivablesturnover and profil margins have a significant influence on economic profitability. Simultaneously shows thatequity, cash turnover, receivables tumover and profit margins are equally influential terhdapa beersama-economic profitability in the Cooperative in Bandar Lampung. Suggestions to convey to the Cooperative boardshould increase the level of accounts receivable tumover, so fast the refund is embedded in receivables into cashback. For further research in order to pay attention to other factors that may affect the profitability of thecooperative economy in Bandar Lampung.